Manejo integrado de la roya Hemileia vastatri, en el cultivo de café Coffea canephora - Vera Araujo, Jorge Geovanny (2020)
Coffee in Ecuador represents one more item for the country's economy, although large areas of coffee are not harvested in Ecuador, it is a source of work for you to make this crop. In recent times the coffee sector has been affected by the presence of coffee rust Hemileia vastatrix, thus reducing its production, this is due to various causes such as: susceptible crops, favorable conditions, labor deficit, poor management control of coffee rust. Many farmers do not know how to face the control of this disease so they are not properly trained, they do not recognize the stages of coffee rust and therefore do not know when to apply the chemical for good control.